2015
DOI: 10.15446/rev.colomb.biote.v17n1.50741
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de un bioinoculante a partir de consorcios microbianos nativos fosfato solubilizadores, en el desarrollo de pastos Angleton (Dichantium aristatum) Titulo en ingles: Effect of bio-inoculant from microbial consortia phosphate solu

Abstract: <strong>Título en ingles: Effect of bio-inoculant from microbial consortia phosphate solubilizing natives in development of pastures <em>(Dichantium aristatum)</em></strong><em></em><p><em></em><strong>Título corto:</strong> <strong>Efecto de un bioinoculante en pastos Angleton</strong></p><p><strong>Resumen</strong>: El objetivo fue evaluar la capacidad solubilizadora de fosfatos de consorcios formados por ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Lara-Mantilla et al. , (2015) and Nandimath et al., (2017) demonstrated bacteria consortia use at 10 × 10 8 CFU mL −1 compared with individual strains and in co-culture increases phosphorus solubilization [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lara-Mantilla et al. , (2015) and Nandimath et al., (2017) demonstrated bacteria consortia use at 10 × 10 8 CFU mL −1 compared with individual strains and in co-culture increases phosphorus solubilization [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other solubilization mechanisms can be activated and eventually bacteria could produce substances that promote plant growth. Lara-Mantilla et al, (2015) and Nandimath et al, (2017) demonstrated bacteria consortia use at 10 Â 10 8 CFU mL À1 compared with individual strains and in co-culture increases phosphorus solubilization [75,76].…”
Section: Growth Curves and Productionmentioning
confidence: 99%
“…There was no antagonism between the PSB strains since they were able to develop without inhibiting each other's growth. This indicated that there was no antibiosis, space competition or nutrient competition . Pérez et al .…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that there was no antibiosis, space competition or nutrient competition. 25 Pérez et al 26 isolated 130 strains capable of solubilizing Ca 3 (PO 4 ) 2 . None exhibited FePO 4 -or AlPO 4 -solubilizing activities, and so they are largely impractical for use in acidic soils.…”
Section: Discussionmentioning
confidence: 99%